Library Dynamics in Nigeria: Challenges and Emerging Trends in Librarianship (Lead City International Journal of Library, Information & Communication Sciences, 2025)
This study examines the evolving trends in librarianship in Nigeria, focusing on socioeconomic factors influencing library development and the challenges they face. The research uses a qualitative design to analyze emerging trends and their impact on library services. The findings reveal a landscape with both significant challenges and encouraging trends. Collaborations and community involvement programs are crucial for the growth of libraries in Nigeria. The study also highlights challenges such as inadequate funding, limited infrastructure, and the digital divide that hinder 21st-century library services. However, emerging trends like digital technologies, Open Educational Resources, and sustainability present opportunities for enhancing library services. The study also highlights innovations in librarianship, such as e-libraries, Integrated Library Systems, and the integration of artificial intelligence. By leveraging these advancements and addressing socioeconomic and policy challenges, Nigerian libraries can continue to play a vital role in education, research, and community development.